TRAIL facilitates cytokine expression and macrophage migration during hypoxia/reoxygenation via ER stress-dependent NF-κB pathway. (February 2017) - Jiang, Yinan; Chen, Xiaoyan; Fan, Mengya; Li, Hui; Zhu, Weina; Chen, Xi; Cao, Chenghua; Xu, Rui; Wang, Yaohui; Ma, Yuanfang
Highlights: TRAIL facilitated macrophage inflammatory factors production macrophage migration after hypoxia and reperfusion. Production of macrophage cytokines induced by TRAIL dependent on activation of NF-κB and ER stress pathway. ER stress signaling pathway contributed to the activation of the NF-κB signaling pathway. Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), which is known as a key molecule to induce cancer cell apoptosis, has also been found to participate in the process of ischemia/reperfusion (I/R) injury. Infiltrated macrophages play dual roles in inflammatory injury and healing following I/R. Whether TRAIL has any effect on macrophages during this process remains elusive. Here we showed that I/R triggered the expressions of TRAIL, DR5 and cytokines (IL-1β, TNFα, CCL-2 and ICAM-1), in addition to macrophage infiltration, which could be abolished by TRAIL neutralizing antibody. In vitro, TRAIL enhanced DR5 expression and facilitated the macrophages migration following hypoxia/reoxygenation (H/R) treatment in a dose-dependent manner via ER stress and NF-κB signaling pathways, which is accompanied by inflammatory factors expression. The increased cytokines production (such as TNFα and IL-1β) stimulated by TRAIL can be blocked by the NF-κB and ER stress inhibitor. The results also suggested that NF-κB activation of macrophages during H/R was regulated by ER stress. Thus, our research present that TRAIL affects functional activities of macrophages during I/R injury, which may be a potential therapeutic target for ischemic heart disease.